Chorioretinal venous anastomosis for non-ischemic retinal vein occlusion - Wang, Yucheng; Wang, Shaolong; Wang, Shiwu; Ding, Min; Zhang, Min; Tang, Jiannan; Deng, Aijun (Frontiers in Ophthalmology, 2022)
Retinal vein occlusion (RVO) refers to the occlusion of central retinal vein or primary and secondary branches, which is caused by multiple factors. Clinical treatment methods include intravitreal drug injection, systemic drug dilatation of retinal blood vessels, local use of steroids and non-steroidal drugs, thrombolysis, hemodilution, retinal laser photocoagulation, vitrectomy with vascular sheath incision, chorioretinal venous anastomosis (CRVA) and so on. At present, most of the commonly used clinical treatment methods are aimed at RVO complications, but chorioretinal vein anastomosis can reflux retinal vein blood through choroid by venous vascular remodeling. There are reports on the treatment of retinal vein occlusion by chorioretinal anastomosis in domestic and foreign literatures. As a treatment method, venous blood can be drained across the vascular occlusion site, which can relieve some factors of retinal vein occlusion anatomically and achieve good therapeutic effects.